Socialization of Making Traditional Balsam From Natural Ingredients Ginger (Zingiber officinale) as An Anti-Pain Medicine in Tanjung Rejo Village Percut Sei Tuan District: Sosialisasi Pembuatan Balsam Tradisional Dari Bahan Alam Jahe (Zingiber officinale) Sebagai Obat Antinyeri di Desa Tanjung Rejo Kecamatan Percut Sei Tuan - Chandra, Putra; Athaillah, Athaillah; Husein, Saddam; Affan Silalahi, Ali; Aini Khairunnisa, Nur; Indrayani Dalimunnthe, Gabena; Sylvia Br. Ginting, Ovalina (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Ginger (Zingiber officinale) is one of the plants used as a medicine that has various benefits for public health. Traditionally, ginger is often used by pounding it and applying it to the affected body part to relieve pain and various other complaints. In addition, ginger can also be processed into a balm preparation that is more practical and easy to use. The purpose of this community service activity is to provide education to the people of Tanjung Rejo Village, Percut Sei Tuan District, North Sumatra, regarding the use of ginger in the form of a balm preparation. The ginger balm distributed to participants was made in the Pharmacy laboratory of the Haji University of North Sumatra. The community service methods used were education and lectures. The results of the activity showed that the material presented about the use of ginger in the form of a balm and how to make the preparation could be well understood by the participants. Participants were also interested in trying to make it independently. This shows that this community service activity has succeeded in increasing the knowledge and skills of the community in utilizing ginger as a medicinal plant.